Preparation and structure of Octenyl succinic anhydride modified waxy maize starch, microporous starch and maltodextrin - Bai, Yanjie (Kansas State University, 2008)
Octenyl succinic anhydride (OSA) modified starch is widely used in emulsion and encapsulation applications. The functionality of OS starch depends on its molecular structure. A systematic study was performed to investigate the reaction of OSA with granular waxy maize (WM) starch, microporous WM starch and soluble maltodextrin. OS starches were prepared in an aqueous slurry system, and the degree of substitution (DS) of OS starches was determined by titration and [superscript]1H-NMR spectroscopy. For both 3% and 50% OSA treatment, OS maltodextrin had higher DS and reaction efficiency (RE) than OSA modified WM starch and microporous WM starch. The maximum DS of OSA modified granular WM starch was 0.14 and the highest DS of OS maltodextrin was 0.27. For the 3% OSA treatment, the RE for WM starch and maltodextrin was ~ 80% and ~100%, respectively. The structure of OSA modified WM starch and the locations of OS groups on anhydroglucose units (AGUs) were studied by [superscript]1H-NMR and [superscript]13C-NMR. As increasing OS substitution, [superscript]13C - signal at C-1 shifted to upper field. In addition, the [superscript]13C - signal at C-6 shifted to downfield when DS reached 0.073. The results suggested that OS groups were predominantly substituted at the O-2 position and started being substituted at O-6 position when DS was 0.073. FT-IR microspectroscopy was used to detect the heterogeneity OS starch products. Native WM starch, OSA modified WM starches (DS=0.019 and 0.073) and a starch blend with native starch to OSA modified WM starch (DS=0.073) ratio of 7:3 were examined. More than one hundred starch granules of each sample were analyzed one by one by FT-IR microspectroscopy. For the OS starch (DS=0.019), 7% starch granules showed carbonyl absorption. For the OS starch (DS=0.073), 99% starch granules showed carbonyl absorption but the intensity varied, indicating that OSA reacted with most starch granules when DS was 0.073. However, the OS contents of individual granules varied. For the starch blend, only 30% starch granules had carbonyl absorption. FT-IR microspectroscopy is a useful tool to detect heterogeneity of OS starch blends containing native starch.
Keywords: Starch; Octenyl succinic anhydride; Chemical modification; Starch structure; Agriculture, Food Science and Technology (0359)